Superdominant Right Coronary Artery with Absence of Left Circumflex and Anomalous Origin of the Left Anterior Descending Coronary from the Right Sinus: An Unheard Coronary Anomaly Circulation - Marcos Danillo Peixoto Oliveira; Fernando Roberto de Fazzio; José Mariani Junior; Carlos M. Campos; Luiz Junya Kajita; Expedito E. Ribeiro; Pedro Alves Lemos (Case Reports in Cardiology)
Coronary artery anomalies are congenital changes in their origin, course, and/or structure. Most of them are discovered as incidental findings during coronary angiographic studies or at autopsies. We present herein the case of a 70-year-old man with symptomatic severe aortic valvar stenosis whose preoperative coronary angiogram revealed a so far unreported coronary anomaly circulation pattern.